Kajian Tipografi dan ilustrasi dalam promosi tarian singa - Chung, Ling Ling. (Universiti Malaysia Sarawak (UNIMAS), 2006)
This research is conducted to study on the usage of typography and illustration in Lion Dance advertisement promotion. There are similarities in the usage of typo and illustration in the current advertisement. Dance can be used as a means of communication and re-creation in reflecting the cultures and traditions of a particular race. Lion Dance is an expressive and energetic kind of dance that is usually performed during Chinese New Year. Typography refers to the placement of alphabets for the purpose of communication, while the illustration refers to visual image. Advertisement plays an important role in promoting and informing the public of the existence of a dance festival. This research will be focused on the elements of graphic that is which are found in the existing Lion Dance promotional campaign. The findings of this study will lead to the creation of the new typography and illustration that will be applied to the advertisement, which are based on Chinese Calligraphy.